Teacher training: History, legal and political bases and educational practices today - Aparicio, Miriam Teresita (2017)
This paper presents the findings of a research study carried out with those who educate educators (teachers). One of the themes addressed are the social representations (SR) that teachers have of the application of the legal bases that have sustained teacher training in Argentina throughout history and which continue to underlie this training in the present day. We look at both the changes and continuities and their link to current educational practice. The methodology used was qualitative (documentary analysis, lexicometric analysis, hierarchical evocations). We established Nodes, categories and subcategories of analysis that reveal which aspects make up the core of teachers’ SR and which are peripheral. Our findings – which do not coincide with the devalued images of teachers presented by the media, clouded by frequent claims by society – could orient transformations from the political, decision-making sector that would seek to improve practices and recover, precisely, the legal bases and their evolution up to the present day.